INTERPERSONAL COMMUNICATION IN SHAPING THE FAMILY CONCEPT SAKINAH, MAWADDAH, WARAHMAH - Citra Ningsih (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2022)
Supportive attitude is the key to success in creating the concept of the Sakinah, Mawaddah, Warahmah family. The attitude of understanding and accepting with positive thoughts from something so that all external stimuli can be received without affecting emotions. Trust is a self-concept, namely a person's belief in himself to trust others because it has an important element in creating the concept of the Sakinah, Mawaddah, Warahmah family. The obstacles encountered in communicating between husband and wife to create the concept of the Sakinah, Mawaddah, Warahmah family are: Emotions, Fear, Anxiety. These three elements affect attitudes when communicating with partners who are motivated by different situations and conditions. The results of this study indicate that effective communication used by family couples in Jombang Regency in forming the concept of the Sakinah, Mawaddah, Warahmah family is interpersonal communication that is effective communication used by family couples in Jombang Regency in forming and fostering the concept of a sakinah family is interpersonal communication. that are open, empathetic, mutually supportive, positive and have equality. The coaching efforts carried out by the two family couples are maintaining a relationship with God by maintaining prayer, putting a problem in deliberation and trying to understand each other, carrying out each other's responsibilities with sincerity, instilling noble character in children from a young age and keep in touch with relatives and neighbours.